Development of biomimetic micro-patterned device incorporated with neurotrophic gradient and supportive Schwann cells for the applications in neural tissue engineering. (28th February 2017) - Yeh, Chia-Wei; Wang, Li-Wen; Wu, Hsi-Chin; Hsieh, Yi-Kong; Wang, Jane; Chen, Ming-Hong; Wang, Tzu-Wei
Abstract: In these years, the artificial nerve guidance conduit (NGC) has been developed as an alternative way to repair peripheral nerve injury. Unlike autologous nerve graft, the artificial NGC without proper stimulating factors and guidance cues still cannot obtain satisfactory prognosis for clinical patients. In this study, a biodegradable polymer-based implantable device has been developed and characterized. By incorporating three stimulating factors: (1) micro-patterned surface that can directionally guide the axon as physical cue; (2) neurotrophic gradient membrane that can continually attract axon outgrowth from the proximal to distal stump as chemical cue; (3) Schwann cells (SCs) that can support the growth of neurite and form myelin sheath around axon as biological cue, we expect that this construct can be used as a promising NGC for peripheral nerve regeneration. The results showed that the micro-patterned surface with specific dimension of channels and chambers can be precisely fabricated by laser ablation. Attachment and directional extension of differentiated neural stem cells (NSCs) were observed in micro-channels. The gradient distribution of nerve growth factor 7S on gelatin membrane was successfully achieved. Significant improvement in neurite length and increase in neuronal gene expressions were also noticed in higher concentration region. When co-culturing with SCs, NSCs can differentiate toward neuronal cells with strong expression of mature neuronal markers: β III tubulin and microtubule-associated protein-2 (Map 2). Meanwhile, myelin basic protein was also observed, suggesting that SCs can provide biological support to neuronal cells in vitro . In the future, this advanced artificial NGC may be used as implantable prosthesis for the treatment of peripheral nerve injury with better functional recovery.